Holocene Glaciation of the Arrigetch Peaks, Brooks Range, Alaska - Ellis, James M.; Hamilton, Thomas D.; Calkin, Parker E. (ARCTIC, 1981)
Eleven cirque glaciers and associated deposits within the granitic Arrigetch Peaks of the west-central Brooks Range face north, minimizing insolation. Shading by surrounding mountainous terrain decreases insolation on these landforms even more significantly, favoring the formation of glacier-cored moraines. Comparison of glacier photographs taken in 1911, 1962, and 1979 reveals a record of decelerating recession. Geomorphic and lichenometric mapping suggests at least three to possibly eight phases of Holocene glacial expansion. These date between ~5000 and 300 yr B.P., based on the application of a central Brooks Range Rhizocarpon geographicum growth curve.